S54. THE RELATION OF FORMAL THOUGHT DISORDER WITH COGNITIVE FUNCTIONS, GLOBAL AND SOCIAL FUNCTIONING AND QUALITY OF LIFE IN PATIENTS WITH SCHIZOPHRENIA. (18th May 2020) - Mutlu, Emre; Abaoğlu, Hatice; Barışkın, Elif; Akı, Esra; Yağcıoğlu, A Elif Anıl; Yazıcı, M Kazım
Abstract: Background: Formal thought disorder (FTD) is considered to be a core syndrome of schizophrenia (SZ). Although there are few studies investigating the cognitive correlates in FTD, etiopathogenesis of this cluster of symptoms is not fully elucidated. Additionally, the impact of FTD on the global and social functioning and life satisfaction is yet unclear. The Thought and Language Disorder Scale (TALD) is a comprehensive, 30-item scale covering both positive/negative and objective/subjective FTD symptoms. Its unique four factorial structure is an excellent advantage to find out the relation between FTD dimensions and cognitive abilities, functioning and quality of life. This study aims to analyze the relationship between FTD which was assessed with TALD and cognitive functions, global, social functioning and quality of life in patients with SZ. Methods: Patients who met DSM-5 criteria for schizophrenia and aged between 18 and 65 years were recruited from the Department of Psychiatry, Hacettepe University Faculty of Medicine. The Turkish version of Thought and Language Disorder Scale (TALD-TR) was administered to detect formal thought disorder symptoms. The Positive and Negative Syndrome Scale (PANSS) and Clinical Global Impression-Severity Scale (CGI) were used to assess psychopathology and illness severity. Cognitive functions were investigated using a neuropsychological test battery (working memory, verbal fluency, abstract thinking, executive functions and response inhibition). The Functioning Assessment Short Test (FAST) and the Social Functioning Scale (SFS) were administered to assess global and social functioning, World Health Organization Quality of Life Instrument Short Form (WHOQOL-BREF) was administered to assess quality of life. Results: The sample consisted of 46 patients (mean age 39.4 ± 10.8) and 39% (N=18) of the participants were females. Mean duration of education was 11.5 ± 3 years and mean duration of illness was 15 years. Partial correlation analyses, controlling for age and duration of education, showed that the Objective Positive FTD was associated with a deficit in executive functions and that the Objective Negative FTD was associated with impairment in working memory, category (semantic) verbal fluency, executive functions, abstract thinking and response inhibition. There was a significant negative correlation between Subjective Negative FTD and verbal fluency (alternation) whereas Subjective Positive FTD was correlated positively with lexical verbal fluency. Although FTD was significantly correlated positively with deficits in social, interpersonal and occupational functioning, no relation was detected between FTD and self-reported quality of life. Discussion: Our findings indicate that the multidimensional symptomatology of FTD could be the result of different cognitive impairments. In line with the literature, both objective positive and objective negative FTD were related to executive deficits. Additionally, working memory, verbal fluency, abstract thinking and response inhibition were correlated with objective negative FTD. To our knowledge, the relation between subjective FTD and verbal fluency is a novel finding in FTD research. Because of the close relationship between FTD and general /social functioning, FTD should be considered as one of the main treatment goals in schizophrenia. It could be suggested that investigating objective quality of life along with subjective assessments could better clarify the effect of FTD on patient's life satisfaction. Comparison with healthy individuals, and future addition of neuroimaging investigations would further support the interpretation of these results.